Sweeteners from Different Lingonberry Jams Influence on Bioaccessibility of Vitamin C, Anthocyanins and Antioxidant Capacity under In Vitro Gastrointestinal Digestion - Teodora Scrob; Anamaria Hosu; Claudia Cimpoiu (MDPI AG, 2022)
Lingonberries are considered anot fully exploited major source of antioxidants. Their health benefits are closely linked to their bioavailability. Due to growing health concerns, consumers are looking for jams prepared with sweeteners other than white sugar, which could be a good alternative to meet their needs. The aim of this research was to evaluate the influence of sucrose, fructose, erythritol, brown sugar, coconut sugar, stevia and saccharine on the bioaccessibility of vitamin C, anthocyanins andthe antioxidant capacity of lingonberry jams under in vitro gastrointestinal digestion. The vitamin C, total anthocyanin content and antioxidant capacity measured by ABTS and FRAP assays were determined spectrophotometrically. Individual anthocyanins were determined by high performance liquid chromatography. All analyzed compounds were highly altered during gastrointestinal digestion and this effect was more visible in the case of the anthocyanins. Antioxidant capacity decreased after gastric digestion, but after the gastrointestinal step, radical scavenging capacity increased, while reducing power decreased. Vitamin C bioaccessibility was negatively affected by coconut sugar addition, while stevia addition showed a protective effect. Fructose and sucrose increased the total anthocyanin stability during the intestinal phase. Stevia, fructose and coconut sugar exhibited high protection of the antioxidant capacity of lingonberry jams during digestion.